Irradiation Sterilized Gelatin–Water–Glycerol Ternary Gel as an Injectable Carrier for Bone Tissue Engineering. Issue 2 (8th November 2016) - Zhao, Yantao; Han, Liwei; Yan, Jun; Li, Zhonghai; Wang, Fuli; Xia, Yang; Hou, Shuxun; Zhong, Hongbin; Zhang, Feimin; Gu, Ning
Abstract : Injectable gelatin gels offer an attractive option for filling bone defects. The challenge is to fabricate gelatin gels with optimal gelation properties, which can be irradiation sterilized. Here, a gelatin–water–glycerol (GWG) gel is reported for use as a broad‐spectrum injectable carrier. This ternary gel is high in glycerol and low in water, and remains stable after gamma irradiation at doses (25 kGy). As an injectable gel, it remains a viscous solution at gelatin concentrations ≤2.0%, at room temperature. Its storage modulus increases dramatically and eventually exceeds the loss modulus around 46–50 °C, indicating a transition from a liquid‐like state to an elastic gel‐like state. This ternary gel ranges significantly in terms of storage modulus (12–1700 Pa) while demonstrating a narrow pH range (5.58–5.66), depending on the gelatin concentration. Therefore, it can be loaded with a variety of materials. It is highly cytocompatible compared with saline in vivo and culture media in vitro. When loaded with demineralized bone matrix, the composites show favorable injectability, and excellent osteogenesis performance, after irradiation. These features can be attributed to high hydrophilicity and fast degradability. These findings justify that this ternary gel is promising as an irradiation‐sterilized and universal injectable delivery system. Abstract : A gelatin–water–glycerol (GWG) gel can be gamma radiation sterilized but a gelatin hydrogel cannot. Gelatin molecules in the GWG gel are compartmentalized into regions of "available glycerol‐free water", as demonstrated by bubble formation in irradiated samples. Local gelatin protein concentration is remarkably increased, resulting in an increased viscosity. Therefore, demineralized bone matrix block can still be loaded into irradiated GWG gel.